Dental magnetic resonance imaging for periodontal indication – a new approach of imaging residual periodontal bone support. (2nd January 2019) - Ruetters, Maurice; Juerchott, Alexander; El Sayed, Nihad; Heiland, Sabine; Bendszus, Martin; Kim, Ti-Sun
Abstract: Objective: The standard imaging techniques used in dentistry consist of two-dimensional radiographic techniques like intraoral periapical (PA) radiographs, bitewings or extraoral panoramic X-rays. Three-dimensional methods, such as cone beam computed tomography (CBCT), are not standard procedures. In several fields of dentistry, such as oral surgery or implantology, dental magnetic resonance imaging (DMRI), a technique without radiation exposure, has already been introduced as a new promising diagnostic tool. The aim of this study was to compare the agreement of DMRI and PA radiographs in measuring residual periodontal bone support. Material and methods: In this study, the residual periodontal bone support of 21 teeth was investigated and compared with DMRI and PA radiographs by two independent raters. Intra-class correlation coefficients (ICCs) were calculated using the software R to identify the intra-rater and inter-rater agreement of the two modalities. Bland–Altman plots were created to directly compare the two methods. Results: Overall, all calculated ICC values showed an excellent intra-rater and inter-rater agreement (>0.9) for DMRI, as well as PA radiographs. Bland–Altman analysis also showed a strong agreement between both diagnostic methods in this study. Conclusions: In conclusion, there was a strong agreement between DMRI and PA. Thus, DMRI proved to be a comparable method to PA radiographs for evaluating the proportion of residual periodontal bone support.